2020
DOI: 10.1128/aem.00242-20
|View full text |Cite
|
Sign up to set email alerts
|

Cytophaga hutchinsonii gldN , Encoding a Core Component of the Type IX Secretion System, Is Essential for Ion Assimilation, Cellulose Degradation, and Cell Motility

Abstract: The type IX secretion system (T9SS), which is involved in pathogenicity, motility, and utilization of complex biopolymers, is a novel protein secretion system confined to the phylum Bacteroidetes. Cytophaga hutchinsonii, a common cellulolytic soil bacterium belonging to the phylum Bacteroidetes, can rapidly digest crystalline cellulose using a novel strategy. In this study, the deletion mutant of chu_0174 (gldN) was obtained using PY6 medium supplemented with Stanier salts. GldN was verified to be a core compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…These results suggest that Ca 2+ and K + might be important for Δ3238 mutant growth. Studies from our group have shown that chu_0174 ( gldN ), chu_0029 ( sprA ), and chu_2709 ( sprT ) deletion mutants in C. hutchinsonii had growth defects in Ca 2+ - and Mg 2+ -deficient media ( Gao et al, 2020 , 2021 ). chu_3238 may also play a role in ion assimilation of Ca 2+ and K + , but not in the assimilation of Mg 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that Ca 2+ and K + might be important for Δ3238 mutant growth. Studies from our group have shown that chu_0174 ( gldN ), chu_0029 ( sprA ), and chu_2709 ( sprT ) deletion mutants in C. hutchinsonii had growth defects in Ca 2+ - and Mg 2+ -deficient media ( Gao et al, 2020 , 2021 ). chu_3238 may also play a role in ion assimilation of Ca 2+ and K + , but not in the assimilation of Mg 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, outer membrane proteins are necessary for C. hutchinsonii to bind and degrade cellulose, and many of these proteins are the components or substrates of the T9SS ( Ji et al, 2012 , 2014 ; Wang et al, 2017 , 2019 ; Zhao et al, 2020 ). The components of C. hutchinsonii , including CHU_0170 (SprP), CHU_3237 (PorU), CHU_0174 (GldN), CHU_0029 (SprA), and CHU_2709 (SprT), were found to affect the gliding motility and cellulose utilization ( Wang et al, 2014 ; Zhu and McBride, 2014 ; Gao et al, 2020 ; Gao et al, 2021 ). In addition, CHU_0174, CHU_0029, and CHU_2709 were found to be essential for the assimilation of Ca 2+ and Mg 2+ ( Gao et al, 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bacteroidetes are an important group of bacteria found in the digestive tract of animals and humans and are also widespread in the environment. Many members of this phylum utilise the type IX secretion system (T9SS) to secrete various effector proteins, such as proteases, adhesins, cellulases, chitin and surface layer proteins [ 1 , 2 , 3 , 4 , 5 , 6 ]. The T9SS is important in the periodontal pathogen, Porphyromonas gingivalis , for the secretion of at least 30 proteins, including its major virulence factors called gingipains (Kgp, RgpA, RgpB) [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cryo-electron tomography revealed filaments and outer membrane-associated patches near the base of the outer membrane of WT cells, but these were not observed when the nonmotile gldF mutant cells were similarly examined [ 8 ]. SprB is secreted and translocated to the cell surface by the Bacteroidetes-specific type IX secretion system (T9SS), which is intertwined with the gliding motility machinery [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Therefore, T9SS mutants influenced gliding and caused nonspreading colonies on both agar surfaces.…”
Section: Introductionmentioning
confidence: 99%